2022
DOI: 10.5713/ab.21.0298
|View full text |Cite
|
Sign up to set email alerts
|

Glycine alleviated diquat-induced hepatic injury via inhibiting ferroptosis in weaned piglets

Abstract: Objective:The beneficial effects of glycine were tested in piglets with diquat-induced hepatic injury.Methods: Thirty-two piglets were assigned by a 2 × 2 factorial experimental design including glycine supplementation and diquat challenge. After 3 weeks of feeding with a basic diet or a 1% glycine supplemented diet, piglets were challenged with diquat or saline. After 1 week later, the piglets were slaughtered and samples were collected. Results:Our results indicated that glycine alleviated diquat induced mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Hence, it is necessary to also verify whether melatonin protects the testes from diquat-induced oxidative stress by regulating SIRT1. Meanwhile, other studies suggest that diquat induces lipid peroxidation [ 61 ], in which hepatocytes and intestinal mucosa ferroptosis were caused following the treatment of piglets for seven days, via regulating the expression of ferroptosis mediators (transferrin receptor protein 1, heat shock protein beta 1, solute carrier family 7 member 11, and glutathione peroxidase 4) [ 62 , 63 , 64 ]. It would, therefore, be of interest to determine whether melatonin reverses testis injury following diquat exposure in a ferroptosis-associated manner.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is necessary to also verify whether melatonin protects the testes from diquat-induced oxidative stress by regulating SIRT1. Meanwhile, other studies suggest that diquat induces lipid peroxidation [ 61 ], in which hepatocytes and intestinal mucosa ferroptosis were caused following the treatment of piglets for seven days, via regulating the expression of ferroptosis mediators (transferrin receptor protein 1, heat shock protein beta 1, solute carrier family 7 member 11, and glutathione peroxidase 4) [ 62 , 63 , 64 ]. It would, therefore, be of interest to determine whether melatonin reverses testis injury following diquat exposure in a ferroptosis-associated manner.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that supplementation of glycine in the diet can increase intestinal GSH content, enhance the intestinal antioxidant level and effectively relieve oxidative stress in mice [ 36 , 37 ]. Moreover, Hua et al found that dietary glycine could increase the activities of T-AOC, GSH-PX, and GSH in the liver, reduce the content of MDA, and alleviate the oxidative stress induced by diquat injection in piglets [ 38 ]. This further illustrated that glycine may improve intestinal antioxidant capacity by increasing the GSH content [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of many studies, it was found that the expression of the GPX4 gene could inhibit iron death and alleviate cell damage [ 43 , 44 , 45 ]. Xu et al have shown that dietary glycine can effectively inhibit the expression of TFR1, a key gene of ferroptosis, and promote the expression of GPX4, thereby alleviating liver injury induced by diquat [ 38 ]. These results suggested that dietary glycine can enhance the synthesis of GPX4, inhibit the occurrence of ferroptosis, and then protect the gut from the damage caused by ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Diquat is a selective herbicide that can induce oxidative stress, karyolysis, karyopyknosis, and changes in hepatic cord arrangement in piglets [ 124 ]. Recent studies showed that holly polyphenols extracts (HPE) [ 124 ] and glycine [ 125 ] could alleviate diquat-induced liver injury by targeting ferroptosis. Mechanistically, they both enhanced GPX4 expression, and HPE also inhibited the transfer of Fe 3+ by decreasing TFR1 abundance [ 124 , 125 ].…”
Section: Nac Treat Liver Disease By Targeting Ferroptosismentioning
confidence: 99%